A participação da sociedade civil na Câmara Municipal de Ponta Grossa (2013-2016): mecanismos legais e a perspectiva de uma democracia participativa - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
The research aimed to investigate how the relationship between civil society and the City Council of Ponta Grossa/PR has operated through the materialization of social participation mechanisms foreseen in the Internal Regulation during the 2013 to 2016 legislature, in addition to the consequent reflections in the perspective of participatory democracy. For this, the different conceptions of State and the movements of approach and / or distancing of civil society with the Liberal State and Social State are used as theoretical support; the categories of participatory democracy and social subjects and the political-electoral formation of the municipality of Ponta Grossa (PR) of the City Council from 2013 to 2016. It is an exploratory research that, through documentary research, aims at the approximation with the empirical reality of the participation of civil society with the Municipal Council of Town Councilors. For the collection of data and using the technique of hermeneutic-dialectical analysis, 402 minutes of the ordinary and extraordinary legislative sessions were read, and of this universe, the participation of civil society was highlighted in 68 legislative sessions, divided in 46 participations through requests formulated by the councilmen and 22 participations through the use of the Free Tribune. The research allowed to infer the existence of the Free Tribune as a mechanism for civil society participation and that, moreover, other constitutional mechanisms of democratic participation were not received or used in the period under investigation.
Keywords: Estado ampliado; Sociedade civil; Democracia participativa; Ponta Grossa; Poder Legislativo; Expanded state; Civil society; Participative democracy; Ponta Grossa; City Council; CNPQ::CIENCIAS SOCIAIS APLICADAS